Calculation of fuel burnup in a VVER-1000 reactor installation - Seken, D.M.; Surayev, A.S.; Irkimbekov, R.A.; Zhanbolatov О.М.; Vityuk G.А.; Mukhamedov N.Е.; Vityuk V.А. (Recent Contributions to Physics, 2025)
The VVER (Water-Water Energetic Reactor) is a type of PWR (Pressurized Water Reactor) widely used in global nuclear energy due to its reliability and high operational performance. In this study, the MCNP6 computer code is utilized to develop a detailed neutron-physical model of the VVER-1000 reactor core and to perform calculations. The primary objective of the research is to accurately reproduce the key characteristics of the reactor. Calculations of the neutron multiplication factor and fuel burnup process in the reactor core were conducted. Special attention was paid to burnup calculations considering the actual power profile during the first fuel cycle. Based on the calculations, changes in the atomic concentration of 235U and 238U in different core zones were determined. The dynamics of plutonium, xenon and samarium isotope concentrations for each type of fuel assembly were also analyzed, enabling the assessment of their impact on the neutron-physical characteristics of the reactor. A comparison of the obtained results with computational and experimental data from literature sources confirms their reliability.